Human Resources in U.S. Healthcare (Journal of Namibian Studies : History Politics Culture, 2024)
Whether clinical or non-clinical, staff involved in the delivery of healthcare are part of the sector’s workforce and human resource. When a healthcare system is funded by the private sector, the workforce dynamics are often affected by the financial flow of these private entities. As such, any cuts in funding would mean limiting the ability to hire and sustain a skilled healthcare workforce. Nations have their own healthcare system and their workforce conforms to the needs and demands of that system. As in the U.S., its healthcare workforce is dictated by the uniqueness of the system. As such, some problems have risen and as perceived by the author, they are as follows: 1) recruitment and retention of professionals, 2) compliance with new standards, 3) incomplete data on migration of healthcare workforce in the U.S., inadequate production levels to ensure workforce supply for future needs, and 5) the privatized nature of the U.S. healthcare system. Globalization has affected the workforce dynamics of the U.S. healthcare. It now sources employees from a global pool. This has opened the doors for people from all nations to jump at employment opportunities in the U.S. However, part of what these prospective employees look for is the wide room for growth often embodied, not just by promotion and incentives, but also by continuous learning and trainings. Because of this, many healthcare agencies have upped their programs on training, equipping people, and improving their current workforce and this has made them more attractive to the global pool of prospective employees. The downside is that, after having trained these employees, healthcare organizations are left on constant lookout for new employees as those they have trained usually move out for better opportunities, elsewhere. The same scenario prevails in the U.S. healthcare sector.